2016
DOI: 10.1016/j.tranon.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Association of Biomarkers with Serious Cardiac Adverse Events during Abiraterone Acetate Treatment in Castration Resistant Prostate Cancer

Abstract: BACKGROUND: Abiraterone acetate is an effective drug for castration-resistant prostate cancer, but cardiac serious adverse events (SAEs) may occur. We studied their association with N-terminal pro–brain natriuretic peptide (NT-proBNP) and troponin T (TnT) during abiraterone therapy. PATIENTS AND METHODS: In a single institution, 17 patients were treated with abiraterone acetate 1 g daily with concomitant prednisone and then switched to dexametasone plus canrenone. Blood samples for PSA, NT-proBNP, and TnT were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Our findings are consistent with published reports showing an increased risk of grade 3 (severe) or grade 4 (life-threatening) cardiac adverse events (AEs) after AA in the general population and clinical trials [20]. A meta-analysis of published randomized controlled trials found that AA was associated with a 2.2-fold risk of cardiovascular toxicity (RR = 2.2, 95% CI: 1.60-3.27); a similar pattern was not observed in ENZ users (RR = 1.32, 95% CI: 0.85-2.06) [21].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with published reports showing an increased risk of grade 3 (severe) or grade 4 (life-threatening) cardiac adverse events (AEs) after AA in the general population and clinical trials [20]. A meta-analysis of published randomized controlled trials found that AA was associated with a 2.2-fold risk of cardiovascular toxicity (RR = 2.2, 95% CI: 1.60-3.27); a similar pattern was not observed in ENZ users (RR = 1.32, 95% CI: 0.85-2.06) [21].…”
Section: Discussionsupporting
confidence: 93%
“…In 2016 Campora et al found an association between higher levels of NT-proBNP and TnT dosed 3 months after initiation of abiraterone therapy and the incidence of severe cardiac adverse events [78].…”
Section: Androgenic Deprivation In Prostate Cancer Patientsmentioning
confidence: 99%
“…More CV events were reported in abnormal hsT and high NTproBNP groups. 38 In our study we draw a different hypothesis that cardiac biomarkers may predict superior response of AA treatment. In our research, D-dimer turned out to be the only marker with prognostic value and to our knowledge this is the first report of such correlation among mCRPC men treated with AA.…”
Section: Discussionmentioning
confidence: 97%